Pemberdayaan Masyarakat Desa dalam Pembuatan Anti Nyamuk Cair Serute (Serai dan Jeruk Monte) - Desy Fadilah Adina Putri; Nurlaila Agustikawati (Jurnal Pengabdian Masyarakat Nusantara, 2025)
One way to prevent mosquito breeding is to limit the number of active mosquito populations and disrupt their life cycle. Preventive efforts to reduce exposure to mosquito bites by using anti-mosquito bed sheets. In several rural areas, people have used lemongrass and Monte orange plants traditionally, but not many have processed them into products with added value. Lack of knowledge and skills in the lemongrass oil extraction process is the main obstacle in developing this potential. The aim of this PKM is to empower the community by making liquid mosquito repellent from local ingredients, namely lemongrass and monte oranges in Labuhan Village, Sumbawa. This community service (PkM) activity will be carried out in November-December 2024 in Labuhan Badas Village, Sumbawa District. This training on making liquid mosquito repellent uses the creative learning method, which is an innovative method that presents material in an interesting and interactive way. The results of community service activities that have been carried out show that the average service activity process reaches 100%. It can be seen that the response from participants in this training was quite high, as shown by the large number of women from PKK cadres and households who attended. Apart from that, this PkM can provide knowledge and skills to mothers so they can complete the use of natural ingredients found around them as natural insecticides.